Relationship Between the Eu and the Central Asian States: Challenges and Opportunities in EU-Central Asian Relationship (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In the 1990s, there seemed to be a complementarity between the needs of the  newly  independent  Central Asian states,  and  the political  and economic interests of the European Union. Yet the EU failed to establish traction in the region and its ability to exert leverage has remained low. One problem is a dissonance in mutual  perceptions, reflecting negative images. Thiscreates  misunderstandings andresentments.The relationship between the EU  and the Central Asian states must be re- calibrated to emphasise partnership not mentorship. Another problem is that EU projects are ambitious in scope but poorly resourced, and thus often fall short of expectations. A third problem is that the EU has been unable to establish itself as a unitary actor in the region. Bilateral links with individual EU member states are more effective. Unless the EU succeeds  in overcoming  its  internal divisions it  will  be  difficult  to implement a coherent regional strategy.